Analisis Indikator Entomologi dan Sebaran Jentik Aedes aegypti pada Daerah Stratifi kasi Endemisitas Demam Berdarah Dengue di Kota Jayapura - Risda Hartati; Tri Baskoro T. Satoto; Elsa Herdiana Murhandarwati; Mutiara Widawati (Loka Litbang Kesehatan Pangandaran, 2021)
The incidence rate (IR) of Dengue Hemorrhagic Fever in Papua Province in 2017 was8.04 per 100,000 population, with a case fatality rate (CFR) of 1.12%. In 2016, the Health Offi ce ofJayapura City declared six urban villages as high endemic areas, four urban villages as high sporadicareas, and ten villages as DHF-free areas from a total of 39 urban villages in Jayapura. This studyaims to analyze larval by House index [HI], Container index [CI], Breateu index (BI), and Maya index[MI] as well as the distribution of vector Ae. aegypti in endemic, sporadic and DHF-free areas inJayapura City. The design of this study was a cross-sectional study. This research was conducted fromJanuary to March 2019. Subjects (375 houses) were surveyed according to WHO guidelines basedon its endemicity stratifi cation. Observations of mosquitos’ larvae were done using visual and singlelarvae methods. The result of this research showed that endemic areas had their HI, CI and BI as muchas 43.3%, 16.5%, and 90.0%, respectively, with density fi gure is six. Sporadic areas had their HI,CI and BI as much as 35.4%, 10.9%, and 57.5%, respectively, with density fi gure is fi ve. DHF-freeareas had their HI, CI, and BI as much as 14.8%, 5.7%, and 35.2%, respectively, with density fi gureis fi ve. The Maya index for endemic and sporadic areas was categorized as moderate, while DHF-freeareas were low.